Remotely piloted aircraft improve precision of capture–mark–resight population estimates of Australian fur seals. Issue 8 (2nd August 2019) - Sorrell, Karina J.; Clarke, Rohan H.; Holmberg, Ross; McIntosh, Rebecca R.
Abstract: Remotely piloted aircraft (RPA or drones) have become a powerful tool for use in spatial and temporal ecology. Major benefits for environmental management, including improved accuracy and precision for population monitoring of fauna, are being realized. We used Australian fur seals ( Arctocephalus pusillus ) as a model system to assess how counts and capture–mark–resight (CMR) estimates derived from RPA surveys compared with both traditionally used ground counts and CMR abundance estimates at two colonies in southeastern Australia. To manage the large volume of data, we implemented a citizen science portal SealSpotter to screen RPA imagery for animals of the target age classes. Capture–mark–resight estimates and direct counts using RPA imagery provided measurable improvement in monitoring precision when compared with traditional techniques. A key methodological assumption of CMR estimates is that there is uniform mixing of marked animals across the focal area. This was also validated using spatial data derived from images and linear models, a novel capability of the RPA technique. Our findings have the potential to improve wildlife monitoring techniques for fur seals and are broadly transferable to a wide range of other animal taxa where CMR techniques are employed. Furthermore, they add to the growing body of evidence that demonstrates the benefits of RPAs for wildlife monitoring exceed those of traditional techniques.